2014
DOI: 10.1097/01.asw.0000445952.83084.a0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiologic Evaluation of Chronic Leg Ulcers

Abstract: The flora of CLUs was predominantly constituted by gram-negative bacteria, and P aeruginosa was the most prevalent. The bacterial load of infected ulcers was higher as compared with the others, although some ulcers with GGT also presented a high load. The interpretation of microbiologic tests based on the swab techniques and even on semiquantitative analysis requires close clinical correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 26 publications
2
29
0
2
Order By: Relevance
“…It is very important to recognize the clinical signs and symptoms of wound infection and avoid the indiscriminate use of antibiotics. 9 According to the reports of Schmidt et al, 24 when comparing the bacterial population in different chronic wounds, only 22% of the venous leg ulcers with a positive culture developed a clinical infection in contrast to 70% of the arterial and diabetic ulcers. We did not perform an in-depth analysis to explore the relationship between the culture result and wound etiology because of a relatively small sample in each wound etiology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is very important to recognize the clinical signs and symptoms of wound infection and avoid the indiscriminate use of antibiotics. 9 According to the reports of Schmidt et al, 24 when comparing the bacterial population in different chronic wounds, only 22% of the venous leg ulcers with a positive culture developed a clinical infection in contrast to 70% of the arterial and diabetic ulcers. We did not perform an in-depth analysis to explore the relationship between the culture result and wound etiology because of a relatively small sample in each wound etiology.…”
Section: Discussionmentioning
confidence: 98%
“…5 However, there has been some debate on the literature regarding the microbiology features and spectrum of chronic wounds. [6][7][8][9] Understanding the microbiological characteristics of different types of chronic wounds may be useful for guiding empiric therapy and managing the patients. 5 In this study, our aims were (a) to investigate the information of chronic wounds, especially in the aspect of microbiological profile and (b) to explore the relationship between the wound culture result and chronic wounds infection in a specialized wound healing department in China.…”
mentioning
confidence: 99%
“…12 No entanto, só por si os critérios microbiológicos não devem ser decisivos para a instituição da terapêutica, sendo necessário a sua correlação com os critérios clínicos. 13 Os antibióticos mais utilizados na última semana foram a flucloxacilina e ciprofloxacina, sendo que a ciprofloxacina não deve ser prescrita nas infeções por Staphylococcus aureos meticilino-resistentes, 8 frequente neste tipo de feridas, 25 infeção que apenas se pode excluir com cultura de bacteriológica com amostra colhida preferencialmente por biópsia. 8,12 No âmbito dos Cuidados de Saúde Primários, para além dos profissionais de enfermagem, é fundamental envolver com regularidade os médicos de família, nutricionista e outros profissionais, no acompanhamento destes doentes, de forma a que numa fase precoce se faça um planeamento adequado de cuidados.…”
Section: Discussionunclassified
“…Os antibióticos, só por si, não são suficientes para o seu tratamento e não há evidên-cia da sua utilidade no tratamento profilático ou de rotina, uma vez que as feridas têm uma flora mista que muda ao longo do tempo. 12 No caso de existirem critérios clínicos de infeção, a antibioterapia sistémica deve ser ponderada conjuntamente com os resultados do exame microbiológico, 12,13 revelando-se de grande importância o treino dos profissionais para a deteção dos sinais clínicos de infeção 12 e de um juízo clínico ponderado.…”
Section: Introductionunclassified
“…15 In another study of chronic leg ulcer microbial swabs, the primary bacteria obtained from 75 patients studied were Pseudomonas, Proteus, and Escherichia coli, with 18 other geneses identified. 16 In a recent review article, Dana and Bauman stated that the most common organisms found in pressure ulcers are S. aureus, Proteus mirabilis, P. aeruginosa, and E. faecalis. 17 With the exception of E. coli, all of the microbes isolated in the reviewed wound studies, excluding E. coli, were also found within the foam dressing extracts in this study.…”
Section: Discussionmentioning
confidence: 99%